Iron Deficiency Anemia in Pregnancy after Bariatric Surgery: Etiology, Risk Factors, and How to Manage It - Carolinade Freitas Alves Amaral-Moreira; Guilherme Redezuk; Belmiro Gonçalves Pereira; Anderson Borovac-Pinheiro; Patricia Moretti Rehder (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2023)
Abstract Objective Pregnancy after bariatric surgery is a reality of the 21st century and therefore is essential that all obstetricians know how to manage it. The most prevalent nutritional deficiency is iron deficiency and, consequently, anemia. Although bariatric surgery and pregnancy are already risk factors for anemia, we evaluated in our study if there were any other risk factors and actions to improve hemoglobin levels in this population. Methods We performed a retrospective cohort study, and performed frequency measurements and analyzes of odds ratio, X2 and Fisher exact test to evaluate the risk factors. Results We evaluated 44 pregnancies after bariatric surgery, with an incidence of anemia of 62%, and the only identifiable risk factor for anemia was being black. As for the treatment, the iron salt used for oral supplementation did not associate with anemia risk, and in 27% of the patients, the adjustment of the oral dosage was enough for improvement in hemoglobin levels, but in 36% supplementation with intravenous iron was necessary. Conclusion Being black is a risk factor for anemia. The type of iron salt does not correlate with the incidence of anemia, and for the treatment and improvement of iron dosages, it seems an effective increase in iron intake.